2005
DOI: 10.1111/j.1553-2712.2005.tb01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Emergency Medicine Resident Debt Status and Financial Planning Preparedness

Abstract: Objectives: Most resident physicians accrue significant financial debt throughout their medical and graduate medical education. The objective of this study was to analyze emergency medicine resident debt status, financial planning actions, and educational experiences for financial planning and debt management. Methods: A 22-item questionnaire was sent to all 123 Accreditation Council on Graduate Medical Education-accredited emergency medicine residency programs in July 2001. Two follow-up mailings were made to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
2
20
1
Order By: Relevance
“…Our findings were similar to those of previous educational studies, where residents from various specialties were mostly described to have high educational debt and limited financial preparedness. 5,6,8,9,11 In our study, we were able to categorize residents' financial behaviors and attitudes in relation to their concern over educational debt. Our data showed that while a significant portion of residents engage in positive financial behaviors, a subset have high debt, lower levels of concern, and fewer positive financial practices compared with their peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were similar to those of previous educational studies, where residents from various specialties were mostly described to have high educational debt and limited financial preparedness. 5,6,8,9,11 In our study, we were able to categorize residents' financial behaviors and attitudes in relation to their concern over educational debt. Our data showed that while a significant portion of residents engage in positive financial behaviors, a subset have high debt, lower levels of concern, and fewer positive financial practices compared with their peers.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Education on financial planning and debt management is important in residency programs, according to surveys of program directors 10 and residents. 11 However, there are few published studies on the effects of financial curricula in residency programs. 3,[12][13][14] Even brief interventions on financial topics were well received by trainees and could change long-term investment behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The American Association of Medical Colleges has recognized financial planning and debt management as important priorities for further education 1,3. A recent survey of surgery residency program directors showed near unanimity in the importance of training residents in financial management,4 and 84% of surveyed emergency medicine residents believe that residency training should include financial planning education 5. Despite these overall attitudes, relatively little is known about how residents actually manage their personal finances.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of all emergency medicine residents conducted in 2001 (67% response rate) revealed that 82% received no financial planning education whatsoever during residency. Among those who received some instruction, in most cases, it was less than five hours [ 10 ]. We did not conduct a formal needs assessment among our learners, but a previously published assessment performed on surgical residents found widespread gaps [ 14 ].…”
Section: Discussionmentioning
confidence: 99%